Mediation Effect of Teaching Factory Implementation on Student Work Readiness with Individual Readiness to Change - Anggitan, Titis; Gunadi (Universitas Pendidikan Ganesha, 2025)
The work readiness of vocational high school (SMK) students is a key indicator of the success of vocational education in meeting the demands of the labor market. However, many SMK students are not yet fully prepared to enter the workforce, both in terms of technical and non-technical skills. The implementation of the teaching factory (TEFA) is expected to enhance students' competencies by providing learning experiences that closely resemble real-world work environments. This study aims to analyze: (1) the effect of TEFA implementation on individual readiness to change, (2) the effect of TEFA implementation on students' work readiness, (3) the effect of individual readiness to change on students' work readiness, and (4) the mediating role of individual readiness to change in the relationship between TEFA implementation and students' work readiness. A quantitative approach with an ex-post facto design was used. Data were collected through questionnaires that had been tested for validity and reliability, and then analyzed using path analysis. The results show that TEFA implementation has a positive and significant effect on both individual readiness to change and students' work readiness. Furthermore, individual readiness to change also has a positive and significant effect on students' work readiness and mediates the relationship between TEFA implementation and work readiness. However, the direct effect of TEFA on work readiness is greater than its indirect effect through individual readiness to change. This study highlights the importance of optimizing TEFA to improve the work readiness of SMK students.